2024
DOI: 10.1186/s40168-023-01727-3
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the interplay between root exudates, microbiota, and rhizosheath formation in pearl millet

Abdelrahman Alahmad,
Mourad Harir,
Sylvain Fochesato
et al.

Abstract: Background The rhizosheath, a cohesive soil layer firmly adhering to plant roots, plays a vital role in facilitating water and mineral uptake. In pearl millet, rhizosheath formation is genetically controlled and influenced by root exudates. Here, we investigated the impact of root exudates on the microbiota composition, interactions, and assembly processes, and rhizosheath structure in pearl millet using four distinct lines with contrasting soil aggregation abilities. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 111 publications
0
2
0
Order By: Relevance
“…Root exudates play an important role in the interaction with soil microorganisms [ 6 ]. Notably, the communication between plants and microorganisms involves a complex web of interactions, with root exudates playing a crucial role in shaping the microbial community [ 7 , 8 ]. Alahmad et al [ 8 ] demonstrated a connection between root exudates, microbial community composition, assembly processes, and co-occurrence networks in the rhizosphere of pearl millet (PM) lines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Root exudates play an important role in the interaction with soil microorganisms [ 6 ]. Notably, the communication between plants and microorganisms involves a complex web of interactions, with root exudates playing a crucial role in shaping the microbial community [ 7 , 8 ]. Alahmad et al [ 8 ] demonstrated a connection between root exudates, microbial community composition, assembly processes, and co-occurrence networks in the rhizosphere of pearl millet (PM) lines.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the communication between plants and microorganisms involves a complex web of interactions, with root exudates playing a crucial role in shaping the microbial community [ 7 , 8 ]. Alahmad et al [ 8 ] demonstrated a connection between root exudates, microbial community composition, assembly processes, and co-occurrence networks in the rhizosphere of pearl millet (PM) lines. They utilized an in situ untargeted metabonomic approach, offering comprehensive insights into the metabolic profiles associated with various compartments of pearl millet and their implications for plant–microbe interactions.…”
Section: Introductionmentioning
confidence: 99%